EFFECTIVENESS OF HIGH INTENSITY INTERVAL TRAINING (HIIT) IN IMPROVING CARDIOVASCULAR FITNESS IN YOUNG ADULTS - Suriah Hanafi; Ikadarny, Ikadarny (Adisam Publisher, 2024)
High Intensity Interval Training (HIIT) has gained widespread attention as a method for improving cardiovascular fitness. This study aims to review existing literature regarding the effectiveness of HIIT in improving cardiovascular fitness in young adults. This literature research involved the collection and analysis of articles published in various scientific journals from 2010 to 2023. The keywords used in the search were